Étude descriptive et comparative d’une population d’adolescents agresseurs sexuels - Jacob, Martine; McKibben, André; Proulx, Jean (Criminologie)

(untitled) (Les Presses de l'Université de Montréal, 1993)
This article presents the results of a descriptive and comparative study of 37 adolescents guilty of sexual agression. These youths had been admitted to a medium security psychiatric hospital for an evaluation of their sexual problem by specialists. None of them received a psychiatric diagnosis. The results are presented for the entire group but the latter was divided into two, based on the criterion of the age of the victim (agressors against children, agressors against adults). There were numerous significant differences observed between the two groups whereas many similarities were noted with groups of adult agressors (agressors against children and agressors against women).